MODEL PREDIKSI SIMPLE MOVING AVERAGE PADA AUTO-SCALING CLOUD COMPUTING - Novian Anggis Suwastika; Praditya Wahyu W; Tri Broto Harsono (Universitas Widyatama, 2015)
[INA]Simple Moving Average (SMA) yang merupakan salah satu metode pada model sistem prediksi yang berbasis time series dengan karakteristik komputasinya yang sederhana dibandingkan dengan metode yang lain. Analisis model prediksi SMA ini akan diujikan pada kondisi stabil dan fluktuatif untuk melihat performansi model dengan parameter uji Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), Availability Operational (AO), Down Time dan Up Time. Hasil implementasi model nilai AO di atas 96%. [EN]Simple Moving Average (SMA), is one method for prediction system model time series based with a simple computational characteristics compared with other methods. Analysis of SMA prediction modelswill be tested in a stable condition and fluctuating to see the performance of the model with test parameters Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), Operational Availability (AO), Down Time and Up Time. Results of the implementation of the model AO value above 96%.